Effects of increasing flow rate on aortic stenotic indices: evidence from percutaneous transvenous balloon dilatation of the mitral valve in patients with combined aortic and mitral stenosis. Issue 6 (December 1996) - Lee, T. M.; Su, S. F.; Chen, M. F.; Liau, C. S.; Lee, Y. T.
Abstract : OBJECTIVES: To investigate the effects of transvalvar flow rate on aortic valve resistance and valve area after percutaneous transvenous balloon dilatation of the mitral valve in a homogeneous group of patients with rheumatic heart disease. DESIGN: Retrospective analysis of 12 patients with combined aortic and mitral stenosis who had undergone balloon dilatation of the mitral valve over a period of 9 years. SETTING: Tertiary referral centre. PATIENTS: Twelve (8 women, 4 men; mean (SD) age 37 (9) of 227 consecutive patients with critical mitral stenosis undergoing transvenous balloon dilation of the mitral valve in the centre also had aortic stenosis, defined as a transaortic pressure gradient of more than 25 mm Hg measured at a catheterisation study before valvuloplasty. INTERVENTIONS: Echocardiographic variables (mitral valve area measured by the pressure half-time method and planimetry, and the aortic valve area derived from the continuity equation) and haemodynamic measurements (cardiac output, left ventricular mean systolic pressure, aortic mean pressure, transaortic valve pressure gradient, mitral valve and aortic valve areas derived from the Gorlin formula, and aortic valve resistance) were assessed before and after transvenous balloon dilatation of the mitral valve. Follow up catheterisation to measure haemodynamic variables was performed one week after mitral valvuloplasty. RESULTS: Mean transaortic flow rate increased 33% after mitral valvuloplasty (from 198 (68) to 254 (41) ml/s, P = 0.002). Aortic valve areas derived from the Gorlin formula were significantly increased from 0.57 (0.12) to 0.73 (0.14) cm2 (P = 0.006) after mitral valvuloplasty. However, aortic valve area and valve resistance derived from the continuity equation were independent of the increase in flow rate after mitral valvuloplasty (from 1.29 (0.35) to 1.30 (0.29) cm2 and from 317 (65) to 259 (75) dyn.s.cm-5, both P = NS). CONCLUSION: The Gorlin-derived aortic valve area tends to be flow-dependent, and continuity equation-derived aortic valve area and catheterisation-derived valve resistance seem to be less flow-dependent. In patients with combined mitral and aortic stenosis, these flow-independent indices are important for decision-making.